Varietal performance of pea (Pisum sativum L.) under peach based agroforestry system in mid hill conditions of Himachal Pradesh - Bhutia, P.L.; Thakur, C.L.; Sarvade, S.; Bhardwaj, D.R.; Kaushal, R.; Bhutia, K.G. (Indian Journal of Agroforestry, 2020)
A study was carried out to evaluate the performance of three varieties of pea grown with different doses of inorganic fertilizers + rhizobium inoculation under three years old peach plantation and open field conditions. 100% recommended dose (RD) of NPK + RIS showed best results in most of the growth and yield attributes of pea crop viz., plant height (cm), number of pods plant-1, number of grains pod-1, pod length (cm), pod breadth (cm), 100 grain weight (g), shelling percentage (%) and total biomass production (g). There was no effect of planting conditions with regard to growth and yield attributes of pea. Variety PB 89 exhibited maximum value in most of the growth and yield attributes of pea except plant height, and shelling percentage for which Solan Nirog exhibited maximum value. From the present investigation, it can be concluded that pea variety PB 89 can be successfully grown under peach based agroforestry system without much reduction in yield as compared to sole cropping and for obtaining maximum yield, seed should be inoculated with rhizobium along with application of 100% RD of NPK. This diversified practice can be a viable option for boosting the economy of farming community.